TYPES OF GRAMMATICAL ERROR ENCOUNTERED IN THE ENGLISH COMPOSITION OF THE THIRD GRADE STUDENTS OF INTERNATIONAL BOARDING SCHOOL AMANATUL UMMAH SURABAYA - Rahula Hananuraga (Jurnal Pendidikan dan Sastra Inggris, 2022)
English has been the foreign language in Indonesia for many years. It is taught from elementary school to university as a second language besides the first language, Indonesia. In senior high school, English is taught as the main subject in which the government has changed the curriculum starting from Curriculum Based on Competence 2004 to KTSP (Educational Unit Level Competence).